A Textual analysis of the metaphors in the "Song of Songs" of the Old Testament - Manalastas, Eden Joy D.; San Jose, Aiza Katrina L. (College of Arts and Letters, University of the Philippines Diliman, 2004)
This study is focused on the assertion that word-class (nouns, verbs, adjectives, adverbs, prepositions) has consequences in metaphorical interpretation. The study aims to use the assertion by Goatly to illustrate the metaphors found in the "Song of Songs" the parallelism between the direct evocation of imagery through nouns, and the direct and concrete relationship of God to His people. The model advocated by Andrew Goatly provides the discussion on the consequences and implications of word-class as regards metaphorical interpretation. The model asserts that nouns are more effective V-terms compared to other word-classes as they (nouns) have spatial dimensions through the vividness of their imagery and their ability to enhance memory, thus resulting in better understanding. The direct evocation of imagery through the concreteness of nouns is parallel to the concrete love of God to His people as shown in His direct relationship with them manifested through Christ. This study will help the readers to analyze metaphors through the implications of word-class. Furthermore, this will help them understand more clearly the nature of the relationship between God and His people, which is never an abstract attribute but a concrete and direct one.